TEACHING ENGLISH IN MULTILINGUAL CLASSROOMS: CHALLENGES AND STRATEGIES IN THE INDIAN CONTEXT - Rajaniprashanth, Ch. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Teaching English in multilingual classrooms presents unique challenges and opportunities, particularly in the Indian context, where linguistic diversity is a defining characteristic. This paper explores the complexities of teaching English in classrooms where students come from varied linguistic and cultural backgrounds. Key challenges include managing multiple first languages, varying levels of English proficiency, cultural differences, and limited access to resources. The paper also examines the impact of mother tongue influence on learning English and the difficulty of fostering inclusivity in heterogeneous classrooms. To address these challenges, effective strategies are proposed, such as leveraging translanguaging, promoting a multilingual approach, using context-based learning, and incorporating culturally relevant teaching materials. The importance of professional development for teachers, along with innovative pedagogical approaches such as task-based learning and collaborative techniques, is emphasized. By balancing linguistic inclusivity and proficiency, this study aims to highlight best practices for teaching English in multilingual classrooms. It highlights the role of a multilingual framework in enhancing language acquisition and fostering a more equitable and engaging learning environment in Indian schools.